Protection from Metabolic Dysregulation, Obesity, and Atherosclerosis by Citrus Flavonoids: Activation of Hepatic PGC1α-Mediated Fatty Acid Oxidation - Erin E. Mulvihill; Murray W. Huff (PPAR Research)
Studies in a multitude of models including cell culture, animal and clinical studies demonstrate that citrus-derived flavonoids have therapeutic potential to attenuate dyslipidemia, correct hyperinsulinemia and hyperglycemia, and reduce atherosclerosis. Emerging evidence suggests the metabolic regulators, PPARα and PGC1α, are targets of the citrus flavonoids, and their activation may be at least partially responsible for mediating their metabolic effects. Molecular studies will add significantly to the concept of these flavonoids as viable and promising therapeutic agents to treat the dysregulation of lipid homeostasis, metabolic disease, and its cardiovascular complications.